Review of effective methods of teaching a foreign language to university students in the framework of online distance learning: international experience - Akhmetzadina, Zulfiya R.; Mukhtarullina, Aigul R.; Starodubtseva, Elena A.; Kozlova, Maria N.; Pluzhnikova, Yulia A. (Frontiers in Education, 2023)
The research goal is to analyze the existing and most frequently used methods and competency-based approaches to distance learning of a foreign language. The tasks are formulated to achieve the goal. They involve classifying the methods of foreign language teaching based on the competency approach and identifying the effective methods. The methodological basis of this research includes methods of analyzing the practical experience of foreign language teaching based on a competency-based approach, synthesis of national and international experience, comparison of national models of the language environment, and generalization of sociological data. As a result of the conducted research, it has been revealed that among various methods, approaches related to information and communication technologies [ICT] are utilized most often. We believe that when teachers conduct courses using synchronous computer-mediated communication [SCMC] tools or platforms, students should be given opportunities to express their opinions. Most teachers recognize the creation of instructional videos as the most effective. According to the students, this type of activity also has the greatest learning effect and stimulates creativity. The scientific novelty of the research is the study of foreign language teaching methods based on a competency-based approach within the framework of online distance learning and the relationship of all interested parties, in other words, teachers, students, and educational institutions.